2021
DOI: 10.1016/j.lungcan.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Veliparib and nivolumab in combination with platinum doublet chemotherapy in patients with metastatic or advanced non-small cell lung cancer: A phase 1 dose escalation study

Abstract: Both combinations of the PARP inhibitor veliparib plus platinum doublet chemotherapy (CT), and the programmed death receptor-1 (PD-1) inhibitor nivolumab plus CT have demonstrated encouraging efficacy for treatment of non-small cell lung cancer (NSCLC). This phase 1 dose-escalation study (NCT02944396) evaluated the quadruple combination of veliparib with nivolumab and doublet CT in patients with unresectable advanced/ metastatic NSCLC. Materials and methods: Patients were enrolled into five dosing cohorts: pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
4
9
0
Order By: Relevance
“…The overall response rate (ORR) reached 27% for cohort with pemetrexed and 17% for paclitaxel. This trial also confirmed the anticipated safety signals with no additional toxicity upon adding veliparib to these regimens ( Clarke et al, 2021 ).…”
Section: Combination Of Parpi and Anti-pd1/pd-l1 Icis—clinical Trialssupporting
confidence: 63%
See 1 more Smart Citation
“…The overall response rate (ORR) reached 27% for cohort with pemetrexed and 17% for paclitaxel. This trial also confirmed the anticipated safety signals with no additional toxicity upon adding veliparib to these regimens ( Clarke et al, 2021 ).…”
Section: Combination Of Parpi and Anti-pd1/pd-l1 Icis—clinical Trialssupporting
confidence: 63%
“…The overall response rate (ORR) reached 27% for cohort with pemetrexed and 17% for paclitaxel. This trial also confirmed the anticipated safety signals with no additional toxicity upon adding veliparib to these regimens (Clarke et al, 2021). PD-L1 is known target for most of the ICIs in use as monotherapies, therefore the impact of PD-L1 expression differences between individuals on the trials involving ICIs and PARPi was probed in an interventional JASPER phase II study [NCT03308942] 2 tested the combination of niraparib and pembrolizumab or dostarlimab on a group of chemotherapy-naïve patients with locally advanced or metastatic NSCLC with no prior PD-(L1) chemotherapy.…”
Section: Combination Of Parpi and Anti-pd1/ Pd-l1 Icis-clinical Trialssupporting
confidence: 62%
“…The combination of veliparib plus carboplatin and etoposide demonstrated improved PFS as first-line treatment in patients with extensive-stage small cell lung cancer ( 59 ). Promising antitumor activity was also observed in patients with metastatic or advanced non-small cell lung cancer receiving quadruple therapy with veliparib, nivolumab, carboplatin and paclitaxel ( 60 ). Moreover, combination therapy with veliparib plus carboplatin and gemcitabine demonstrated promising PFS and response rates in ovarian cancer patients with germline BRCA mutations ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 25 patients enrolled; 6 patients received veliparib + nivolumab + carboplatin/paclitaxel and 19 received veliparib (dose-escalated) + nivolumab + carboplatin/pemetrexed. All 25 patients (100%) who received treatment experienced at least one TRAE, of which 18 patients (72%) experienced at least one Grade 3–4 TRAEs leading to 6 patients (24%) discontinuing treatment [ 147 ]. Five patient (20%) deaths, 4 due to disease progression and 1 for unknown causes, occurred within 100 days of receiving the last treatment dose, but none were reported to be treatment-related [ 147 ].…”
Section: Clinical Trials Of Combination Parpi Therapymentioning
confidence: 99%